Response-Guided Low-Temperature Radiofrequency Ablation Without Escalation Above 60°C for Trigeminal Neuralgia: Two Case Reports - Rizky Ramadhana; Rahendra Rahendra (Journal of Society Medicine, 2026)
Introduction: Radiofrequency ablation (RFA) is an established interventional treatment for trigeminal neuralgia refractory to pharmacotherapy. Conventional protocols often escalate the temperature stepwise to 70–80°C; however, higher temperatures increase the risk of sensory complications. Whether selected patients can achieve pain control without escalation above 60°C remains clinically relevant. Case Description: We report two patients with idiopathic trigeminal neuralgia of the mandibular (V3) division treated using a response-guided, low-temperature, fluoroscopy-guided RFA strategy. A 58-year-old man (baseline Numeric Rating Scale [NRS] 8) received two lesions at 50°C for 60 seconds each; a 63-year-old woman (baseline NRS 10) received two lesions at 60°C for 60 seconds each. Both had persistent pain despite paracetamol and pregabalin. Needle placement through the foramen ovale toward Meckel's cave was confirmed fluoroscopically, with sensory and motor testing. Both patients achieved complete pain relief immediately after the procedure (NRS 0), sustained at the three-month follow-up, without corneal complications, dysesthesia, motor deficits, or other adverse events. Conclusion: Response-guided low-temperature RFA without escalation above 60°C may provide effective short-term pain relief in selected patients with idiopathic trigeminal neuralgia while minimizing unnecessary thermal exposure to healthy tissues. Prospective studies are needed to define the optimal patient selection, temperature, and long-term durability.